2022
DOI: 10.1136/bmjopen-2021-055796
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the effectiveness, safety and tolerability of interventions for depressive symptoms in people with multiple sclerosis: a systematic review and network meta-analysis protocol

Abstract: BackgroundComorbid depression is prevalent in people with multiple sclerosis (MS). Depression is commonly untreated or undertreated, thus, there is a need for effective and safe interventions and current guidelines recommend psychological and pharmaceutical interventions for people with MS. However, research suggests that other interventions, such as exercise, could also be effective. The comparative efficacy and safety of intervention modalities have not been quantified.We plan to conduct a systematic review … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…Our patient had an outstanding recovery, which we believe was achieved, at least in part, through daily performance of simple physical therapy. By a network meta-analysis of randomized controlled trials, recent studies have shown the positive effects of motion exercises on improving impaired motor functions of patients with multiple sclerosis (MS) [ 24 , 25 ], the most common demyelinating disorder of the CNS. In an animal model of CNS demyelination, Jensen et al demonstrated, at the histological level, that exercise actually accelerates oligodendrogenesis and the rate of remyelination [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our patient had an outstanding recovery, which we believe was achieved, at least in part, through daily performance of simple physical therapy. By a network meta-analysis of randomized controlled trials, recent studies have shown the positive effects of motion exercises on improving impaired motor functions of patients with multiple sclerosis (MS) [ 24 , 25 ], the most common demyelinating disorder of the CNS. In an animal model of CNS demyelination, Jensen et al demonstrated, at the histological level, that exercise actually accelerates oligodendrogenesis and the rate of remyelination [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…This report highlights that physical therapy, the pivotal roles of which are already established in various neurological disorders, including stroke [ 35 ], Parkinson’s disease [ 36 ], and MS [ 24 , 25 ], is also quite important for improving the prognosis of CPM. Considering the broad spectrum of the effects of exercise on human health, this subject warrants further clinical and basic research.…”
Section: Discussionmentioning
confidence: 99%